Comparison between EM1 and EM4 in improving paddy growth performance / Mohd Zulhamizzan Zakaria - Zakaria, Mohd Zulhamizzan (Faculty of Plantation and Agrotechnology, 2017)
Effective Microorganism (EM), a culture of coexisting beneficial microorganism predominantly consisting of lactic acid bacteria, photosynthetic bacteria, yeast, fermenting fungi, actinomycetes are claimed to enhance microbial turnover in soil thus known to increase soil micronutrients and increase plant growth and yield. EM-1 is the original trademark product and contains a group of bacteria primarily lactic acid bacteria (lactic acid produced in metabolism), yeast, and photosynthetic bacteria while EM-4 consisted of 90% Lactobacillus spp. (1 billion per gram of fluid) that produce lactic acid and culture in liquid medium was acidic pH of 4.5. The main purpose is to know which one will give a large impact among EM-1 and EM-4 on Oryza sativa growth performance. Aerobic and anaerobic respiration co-exist symbiotically is the most beneficial thing to earn belonging EM outstanding features. Both treatments was conducted on the effect of paddy rice for her based on weeds control, pest and disease control, propagation and growth and in terms of soil improvement for common effectively. We can conclude that EM-4 is the best treatment due to latest formulation to produce an output in terms of enhancement crop production and income farmer.